Respuesta :

sxpr
A good one is. 9+10 = 21

r + (-6) = -10

To solve the equation r + (-6) = -10, since -6 is being added to r, we need to subtract -6 from both sides of the equation.

It's important to understand that minus a negative means the same thing as plus a positive so we're really adding 6.

On the left side of the equation, the -6 and +6 cancel out and we have r. On the right side of the equation, -10 + 6 is -4.

So we have r = -4 which is the solution to our equation.

Otras preguntas